Effect of complete feed starch banana weevil pea stone on the beans goats system in vivo against carcass weight and carcass part - A. Aswandi; C. I. Sutrisno; M. Arifin; Joelal Achmadi (Chemical Engineering Diponegoro University, 2012)
The objective of this research is to study the value of benefits in favor of complete feed production performance and carcass weight of any part of the carcass part-goat nuts. The design used in this study. Random Draft Complete. The material used in this study of 12 male goats Nuts averaging initial body weight (15.58 ± 2.601 kg) with a CV: 16.69%, age 10-15 months. At the end of the study 12 goats to know the weight of nuts cut carcass and parts of the carcass. Results of analysis of variance showed that treatment of complete feed on a significantly different (P <0.05) on carcass weight produced goat nuts. Results of analysis of variance showed that treatment of complete feed on a significantly different (P <0.05) against the weight of all the parts ice nuts goat carcass neck, shoulder, breast, leg chump on, ribs, loin, fore shank and the weight of the flank. CF0 and CF3 treatment effects did not provide a very real difference to the weight of carcass parts, but the weight of the carcass are treated CF3 higher than the CF0. This is in line with the expressed [Keywords— banana weevil stone, complete feed goat bean]